2019
DOI: 10.1103/physreve.99.032136
|View full text |Cite
|
Sign up to set email alerts
|

Heat current rectification in segmented XXZ chains

Abstract: We study the rectification of heat current in an XXZ chain segmented in two parts. We model the effect of the environment with Lindblad heat baths. We show that, in our system, rectification is large for strong interactions in half of the chain and if one bath is at cold enough temperature. For the numerically accessible chain lengths, we observe that the rectification increases with the system size. We gain insight in the rectification mechanism by studying two-time correlations in the steady state. The prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…Lastly, because the dominating gmodes are excited at frequencies higher than the most sensitive band of ground-based GW detectors (≈ 70 Hz), larger f a have larger ∆(δφ a ) and ∆( f a ) and thus worse detectability. This is different from the results in Balachandran & Flanagan (2007) who found that increasing f a would make the detection easier, as Balachandran & Flanagan (2007) considered modes that were excited at frequencies lower than the most sensitive band.…”
Section: Modeling the Detectabilitycontrasting
confidence: 70%
See 2 more Smart Citations
“…Lastly, because the dominating gmodes are excited at frequencies higher than the most sensitive band of ground-based GW detectors (≈ 70 Hz), larger f a have larger ∆(δφ a ) and ∆( f a ) and thus worse detectability. This is different from the results in Balachandran & Flanagan (2007) who found that increasing f a would make the detection easier, as Balachandran & Flanagan (2007) considered modes that were excited at frequencies lower than the most sensitive band.…”
Section: Modeling the Detectabilitycontrasting
confidence: 70%
“…Similar to Balachandran & Flanagan (2007), who also studied the detectability of mode resonances (see also Flanagan & Racine 2007), we assume that the frequency-domain GW signal has the form…”
Section: Modeling the Detectabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the use of local Lindblad baths may result in apparent violations of the second law of thermodynamics [123]. Global Lindblad dissipators are free from such problems and can be used to simulate heat transport (see e.g., [124]), but are not practical in that they are limited to very small system sizes. Furthermore, for the description of quantum heat engines in the extreme case where the working medium may even consist of a single two-level quantum system, it is crucial to take into account medium-reservoir quantum correlations as well as non-Markovian effects, which are not included in the standard, weak-coupling Lindblad description of quantum open systems.…”
Section: Overviewmentioning
confidence: 99%
“…Understanding transport properties in quantum systems can lead to various interesting applications such as quantum rectifiers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], transistors [ 14 ], engines [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], refrigerators [ 32 , 33 , 34 , 35 , 36 , 37 ], and batteries [ 38 , 39 , 40 ]. In thermoelectric systems, one main goal is to achieve an electric current due to a temperature bias.…”
Section: Introductionmentioning
confidence: 99%